Fatigue Analysis of Al/Fly Ash Composite from Coal Waste - Gustini Lukman (Sriwijaya International Seminar on Energy-Environmental Science and Technology, 2014)
Hot isostatic pressing is one of the method applied in powder technology to produce high density material. This research aims to investigate physical and mechanical properties of aluminium-fly ash composite made by hot isostatic pressing. Material uses was aluminium powder ( 53 Î¼m)as matrix and fly ash powder as filler ( 53 Î¼m). Fly ash powder was calcined at 800o C for 3 hours. Aluminium and fly ash composition were 95%, 100%, and 5%, 0 % weight fraction. Mixtures were stirred for 5 hours and pressed using 50 MPa and 100 MPa pressure to obtain green compacts. Te green compacts were hot isostatically pressed by 120 MPa pressure at temperature variation of 520o C, 540 oC, and 570 oC using 1 hours holding time. Fatigue analysis showed that optimum fatigue resistance was obtained at composition of aluminium95%-5% fly ash composite made by hot isostatic pressing at 540 oC, 120 MPa pressure, and 1 hours holding time. This composite produced minimum fatigue rate of 0,005 mm3/Nm. The specimen experienced in situ reaction caused by aluminium oxidation during sintering process.